GAMBARAN STATUS GIZI TERHADAP SIMTOM DEMENSIA PADA PASIEN LANJUT USIA DI POSYANDU LANSIA PUSKESMAS KAMPUNG BARU KOTA MEDAN - MAWARNI SIAHAAN; LITA SEPTINA (LP2MTBM MAKARIOZ, 2020)
Dementia is a neurodegenerative syndrome that arises due to proactive abnormalities and progression with multiple sublimefunctions such as calculations, learning capacity, language and decision making. The awareness of dementia is notdisturbed. Impaired cognitive function with worsening emotional control, motivation and motivation. Nutritional status is oneof the factors that cause dementia. To describe the nutritional status of dementia symptoms in elderly patients. This studywas a descriptive study with cross-sectional design and data collection was carried out approach using BMI, MNA andMMSE data obtained from 57 samples. This research was conducted at the Kampung Baru Health Center in Medan City.The study was conducted during April - December 2018. The results of this study showed the majority of elderly patients whohad normal nutritional status based on BMI, the risk of malnutrition based on MNA and had the results of MMSE scores thatwere probable for dementia symptoms. Elderly patients who have poor nutritional status and have the highest risk ofmalnutrition have a probable picture of decreased cognitive function.